1998
DOI: 10.1038/sj.leu.2401080
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor/scatter factor (HGF/SF) affects proliferation and migration of myeloid leukemic cells

Abstract: Hepatocyte growth factor (HGF), also known as scatter factor (SF), is produced by mesenchymal cells, including bone marrow (BM) stromal cells, and has mitogenic and motogenic effects on a variety of cell types. Recently, a role has been assigned to HGF/SF and its receptor, c-MET, in both normal and malignant hemopoiesis. We investigated the function of HGF/SF on hemopoietic mononuclear cells (MNC) from patients with acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) with circulating blasts. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…Interactions between AML cells and bone marrow stromal cells have been described to play an important role in inhibition of apoptosis and in increased proliferation observed in AML clonogenic cells. 66,[69][70][71][72][73] Thus, we assume that reductions in leukemic blasts observed are due to suppression of c-kit signaling. However, the data obtained did not detect an obvious correlation between expression and/or activation of c-kit on leukemic blasts and clinical response to imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between AML cells and bone marrow stromal cells have been described to play an important role in inhibition of apoptosis and in increased proliferation observed in AML clonogenic cells. 66,[69][70][71][72][73] Thus, we assume that reductions in leukemic blasts observed are due to suppression of c-kit signaling. However, the data obtained did not detect an obvious correlation between expression and/or activation of c-kit on leukemic blasts and clinical response to imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…40 Furthermore, the possibility that HGF was produced by leukemic cells in vivo was suggested by the detection of HGF expression and production by freshly prepared AML blasts. Based on these observations, it is not surprising that HGF plasma levels in our study group correlated strongly with the white blood cell counts.…”
Section: Discussionmentioning
confidence: 99%
“…Other interesting gene changes between 2 and 3.5-fold include (Supplementary Table S2) the c-met proto-oncogene (c-met, 3.1-fold) that is the receptor for hepatocyte growth factor, 26 which is also induced eightfold, suggesting that this known oncogenic signaling pathway is putatively upregulated. In addition, as no increased apoptosis was observed associated with decreased Bcl2 (À2.6-fold), it could be suggested that the HGF/c-met signaling pathway may be blocking such a cellular response.…”
Section: Identification Of Genes Altered By Aml1-eto9a In Microarraymentioning
confidence: 99%